Educação antirracista na licenciatura em geografia da Universidade Estadual de Goiás : transformações na matriz curricular e na prática docente - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
The erasure of Black history, knowledge, and practices in Brazil is a way of keeping Black and brown people subordinated in their relationships and territorialities, affecting pedagogical choices and curricular formulations. Although, in recent years, including through the provision of Law 10.639/2003, Afro-Brazilian history and culture have become part of the guidelines and foundations of education, the nuances of pedagogical practices involving anti-racist education are still recent and constantly being (de)constructed. Specifically, the aim was to: Delimit a set of authors and works by classical and contemporary geographers and educators who stand out in the study and theorizing of the racial issue; evaluate the effects of the presence or absence of these authors, themes, and works in the curricula of geography courses; and present contributions to anti-racist geographic education. This research is justified by the need to develop practices and content that value Afro-Brazilian knowledge and contribute to the training of critical teachers, aligned with constitutional commitments and human rights. Research Problem: How has Geography teacher training at the State University of Goiás (UEG) incorporated the anti-racist agenda into its curricula (2015 and 2020 curricular matrices)? General Objective: To analyze how the UEG Geography undergraduate curriculum incorporates anti-racist education. Specific Objectives: 1. To understand the historical foundations and legal bases for combating racism in Brazil; 2. To identify the extent to which the curricular matrices (2015 and 2020) include ethnic-racial content; 3. To evaluate anti-racist teaching practices and pedagogical proposals through discussions, readings, and interviews; 4. To propose recommendations to improve the cross-curricular incorporation of the anti-racist agenda. The research uses a qualitative approach, combining: a bibliographic survey of authors on critical geography, ethnic-racial studies, and legislation; a documentary analysis of the syllabi and pedagogical projects of the geography curricula (2015 and 2020); a semi-structured interview with Professor Dr. Lorena Francisco de Souza, to gather perceptions and pedagogical practices; participation in events and spaces for dialogue and construction of anti-racist education, such as: "Pretagogy in the Formation of Black Identity" (Grupo Anime, UFJF); "Anti-Racist Education" with Professor Bárbara Carine Soares Carneiro (UFBA); studies promoted by Grupo Dona Alzira; musical performances showcasing Black culture at academic and cultural events, among others. The dissertation was structured as follows: Chapter 1: Racism/Enslavement/Ideologization; Chapter 2: The Geography Course at the State University under Discussion: A Proposal for Anti-Racist Education? Chapter 3: Thinking about Teaching Practice and Anti-Racist Educational Approaches; 4: Considerations on the Interview with Professor Dr. Lorena Francisco de Souza; 5: Final Considerations; References and Annexes.
Anti-racist education in the degree in geography at the State University of Goiás : transformations in the curricular matrix and in teaching practice
Keywords: Geografia antirracista; Geografia crítica; Pretagogia; Antiracist geography; Critical geography; Pretagogy; CIENCIAS HUMANAS::GEOGRAFIA